NARRATIVA DAS MULHERES NEGRAS ARTESÃS DO POTY VELHO: SUAS SINGULARIDADES NO ARTESANATO EMPREENDEDOR - Lima de Carvalho, Marlene; Santos da Silva, Mirian; Batista Abade, Soledade; Saraiva de Arêa Leão Sousa, Maryneves (Revista Form@re - Parfor/UFPI, 2026)
.